2009
DOI: 10.1128/iai.00279-09
|View full text |Cite
|
Sign up to set email alerts
|

Sialic Acid Catabolism Confers a Competitive Advantage to Pathogenic Vibrio cholerae in the Mouse Intestine

Abstract: Sialic acids comprise a family of nine-carbon ketosugars that are ubiquitous on mammalian mucous membranes. However, sialic acids have a limited distribution among Bacteria and are confined mainly to pathogenic and commensal species. Vibrio pathogenicity island 2 (VPI-2), a 57-kb region found exclusively among pathogenic strains of Vibrio cholerae, contains a cluster of genes (nan-nag) putatively involved in the scavenging (nanH), transport (dctPQM), and catabolism (nanA, nanE, nanK, and nagA) of sialic acid. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
188
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(198 citation statements)
references
References 82 publications
8
188
1
1
Order By: Relevance
“…The type III secretion systems most frequently found in V. cholerae serogroups non-O1/non-O139 induce severe diarrhea in cholera infection models (29), and this secretion system has been reported in V. cholerae strains that encode and express the O1-antigen (15). Our results are consistent with previous studies that showed VPI-2 to be highly heterogeneous in clinical and environmental strains (15,28).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The type III secretion systems most frequently found in V. cholerae serogroups non-O1/non-O139 induce severe diarrhea in cholera infection models (29), and this secretion system has been reported in V. cholerae strains that encode and express the O1-antigen (15). Our results are consistent with previous studies that showed VPI-2 to be highly heterogeneous in clinical and environmental strains (15,28).…”
supporting
confidence: 83%
“…That is, the VPI-2 locus in non-O1/O139 strains lack most of the VPI-2 ORFs, including the type 1 restriction modification system and mu-like phage regions (Table S3). Interestingly, the sialidase has been shown to unmask the GM1 gangliosides of human intestinal epithelial cells, thus making them more available to CT (28). However, because many of these strains do not encode CT, the high level of conservation of sialidase among these strains suggests an additional role for sialidase in the life cycle of Vibrio.…”
mentioning
confidence: 99%
“…The ripR gene (the gene encoding for ribose phosphate isomerase regulator) in this cluster has been predicted to encode a repressive regulator (11). The V. cholerae (O1 biovar El Tor strain N16961) ripR protein shares 79% identity with V. vulnificus NanR (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli, Vibrio cholerae, Vibrio vulnificus, and Staphylococcus aureus can grow by using Neu5Ac as a sole carbon source (10)(11)(12)(13), and the N-acetylneuraminate (nan) genes responsible for Neu5Ac utilization are up-regulated during their growth on mucus or in the mammalian intestine (3,14). The colonization and pathogenic activities of these bacteria are affected severely by mutations in the nan genes (3,12,15).…”
mentioning
confidence: 99%
“…Sialic acid is ubiquitously found in mucus-rich areas of gut and lung and it can be utilized as a sole carbon and energy source by pathogenic and commensal bacteria (Severi et al, 2007;Almagro-Moreno & Boyd, 2009). A cluster of genes involved in scavenging, transport and catabolism of sialic acid have been identified in V. cholerae; one of the genes of this cluster encodes neuraminidase (NanH), which plays an important role in making sialic acid available to bacteria as a carbon source and in binding of cholera toxin to sialogangliosides (Galen et al, 1992).…”
Section: Discussionmentioning
confidence: 99%